Measuring the performance of ASEAN Islamic bank a non-parametric approach: Data Envelopment Analysis (DEA) / Siti Noorhafiqah Hussain - Hussain, Siti Noorhafiqah (2013)
The Islamic banking environment has grown tremendously over the past several years and will continue to grow to allow better growth of economy. The study is to identify the efficiency change or improvement of Islamic Bank’s performance during the period of 2004-2010. Specifically, the purpose of the study is to measure the efficiency of Islamic Bank’s performance in ASEAN country. The data consists of 21 Islamic banks in ASEAN; Malaysia, Indonesia, Singapore & Brunei Darussalam. The efficiency of the Islamic bank’s performance is measured by using Data Envelopment Analysis (DEA) approach with a specification of input and output variables. The finding suggest that during the period of study, scales inefficiency dominates pure technical inefficiency in the ASEAN Islamic banking sector. We found that the Islamic banks have exhibited higher pure technical efficiency compare to its technical efficiency. The results seems to suggest that the technical efficiency tend to be much more sensitive to the economy factors